RESEARCH ON CHARACTERISTICS OF DAMPING PARAMETERS OF SANDWICH STRUCTURE OF MACHINE TOOL COMPONENTS BASED ON MODAL ANALYSIS - HU Jun; ZHU WenFeng; XU KaiLe; MA ZhuangZhuang (Jixie qiangdu)
The dynamic characteristics are important factors that affect the accuracy of machine tools. Currently,the material combinations are an effective method that is often used. In order to research the dynamic characteristics of machine tool components,the sandwich structure of bolted joint was fabricated. Based on the theory of experimental modal analysis,the TST5912 dynamic signal testand analysis system was used to conduct hammering experiment on the structural parts with HT200 and QT500 materials as the base and constrained layer,the nitrile rubber（ NBR） and polypropylene（ PP） plate as the sandwich materials. By changing the base material,the constraining layer material,the sandwich material and the thickness,the parameters such as vibration mode,natural frequency and damping ratio of the sandwich structure are obtained. The experimental results show that the damping ratio of the rubber sandwich structure is larger than that of the plastic sandwich structure,and increases with the increase of the sandwich thickness. The thinner the base layer,the greater the increase rate of the damping ratio of sandwich structure components.